Determinants of initial payment claim by road accident vicitims - Amnuay Suksong (Chulalongkorn University, 1999)
This thesis concerned with the characteristic of determinants determining an initial payment claim for medical treatment expenses according to The Protection for Motor Vehicle Accident Victim Act BE 2535, and its relation to payment mechanisms. The determinants underlying the analysis is the characteristic of person involved, the actual accident, and some hospital characteristics. The prospectivel cohort road accident victim interview has been designed for data collection from patients admitted to public hospital in Trang province during 5-19 April 1999. The data is used to estimate by a logit model, (The characteristics that determine an initial payment claim: personal characteristics, accident characteristics, and hospital characteristics), and descriptive analysis to explain their payment mechanisms from several funds. The main empirical result of the study is that the characteristics that determinate an initial payment claim for the accident victim is responsive to sex, privilege for healthcare service, a car insurance contract, driver license, police notice, type of patient and the patients department. Only 39.44% of road victim claim an initial payment expense of up to 15,000 baht from the insurance company. The remainder comes from other funds. The results of this study indicate that the determinants of claim should be concerned to induce more protection for the road accident victims. The insurance company and Compensation fund should also be encouraged to respond by making an initial payment for medical treatment expenses with a no-fault system. This study has its limitations. The data were collected in a short period of time which may place bias on the seasonal variation of the incidence rate of road accident and the analysis was based only on road victims perspective, it may therefore not a cover all problems.